A nationwide study of the influence of training institutions in the postgraduate year training program for dentists on the future dental practice choices in Taiwan - Ting-Chen Chen; Wender Lin; Chen-Ying Wang; Shih-Pi Lin; Chiung-Wen Hsu (Journal of Dental Sciences)
Background/Purpose: The postgraduate year training program for dentists (PGYD) provides the comprehensive clinical training to bridge the gap between the academic education and the hands-on clinical practice. This study mainly explored the influence of training institutions on the future dental practice choices (in clinics or hospitals) after the completion of the PGYD program in Taiwan. Materials and methods: A nationwide, register-based cohort analysis was conducted on all 3,966 PGYD trainees from July 2010 to April 2023. Data on the training time, institution type, and demographic characteristics were extracted from the PGYD and dentist registration systems. Chi-square tests and t-tests were used to assess the differences in the future dental practice choices and the PGYD training variables. Results: For the PGYD training institutions, the dental clinics increased substantially, while the medical centers and teaching hospitals declined. The trainees who spent more time in the dental clinics were more likely to practice in the dental clinics, while those trained in the hospitals were more likely to choose the hospital-based practice (P < 0.001). The male dentists were more likely to practice in the dental clinics and the female dentists were prone to practice in the hospitals (P < 0.001). Conclusion: The type and duration of the PGYD training significantly influence the future dental practice choices, with trainees who undergo more clinic-based training tending to choose dental clinic practice. However, the hospital-level training remains crucial for the specialty development, and further policy efforts are needed to improve the imbalance in the dentist distribution.